An exploration of the influence of Khelobedu dialect on standard Sepedi : the case of students writing in a Sepedi classroom context of the University of Limpopo - Letsoalo, Mmaranti Pamla (My University, 2021)
This study explores the influence of the Khelobedu Dialect on Standard Sepedi with a special focus on the students’ writing. A classroom is a space where students need to feel the confidence to take part in classroom activities, language should not be a barrier. Post-1994, South Africa had to take quick measures to redress the injustices that were implemented towards indigenous languages by the previous government. This meant that South African indigenous languages were elevated to official status. Part of this process of officiating indigenous languages of South Africa was based on the concept of language planning which required that official languages must have orthography. This meant that those dialects which did not have orthography could not form part of the standardisation process. Khelobedu is one of the dialects in Sepedi which was left out during the standardisation of Sepedi. This was because of the settlement of the missionaries in South Africa. With the growing need to promote multilingualism and to use indigenous languages for learning and teaching, students who speak Khelobedu as a first language face challenges in the Multilingual classroom where Sepedi is used as a medium of instruction. Instruments such as individual interviews, focus group interviews and document analysis was used to gather data for this qualitative study. The data for this study has revealed that students face various challenges in the Multilingual Studies classroom, in the individual interviews participants have highlighted challenges such as phonological, spelling and finding relevant terminologies from their first language to the standardised Sepedi. The data from the focus group has revealed that most of the participants agree that these challenges are predominant. Both types of interviews revealed that participants will appreciate having orthography from the first language be added to the standard Sepedi. Document analysis instrument data has revealed the challenges that the students face in the Multilingual Studies classroom. With the current trends in Higher Education where education is evolving and issues of inclusivity are of importance, the study suggests a model for the re-standardisation of Sepedi where orthography from Khelobedu can be added through the process of corpus language planning.
Thesis (Ph.D. (Translation Studies and Linguistics)) -- University of Limpopo, 2021
Keywords: Influence of Khelobedu dialect; Sepedi language; Sepedi classroom; Northern Sotho -- Dialect; Standardization; Northern Sotho language -- Standardization; Northern Sotho -- Dialects